Modern backbone elements of the subject of the agrarian law of Ukraine - Савельєва, О. М. (Theory and practice of jurisprudence, 2016)
The article analyzes the problems of the modern science of Agrarian Law of Ukraine. Investigate the structure of the subject of the agrarian sector of Ukraine Law, focuses on the dynamic development of public relations in the sphere of development of the agricultural sector, in particular with regard to the production and sales of organic agricultural production, ensure food security of the state, and so on are given suggestions about the content of the modern category of the subject of legal regulation of the agrarian law of Ukraine.